2012
DOI: 10.5539/ijel.v2n1p47
|View full text |Cite
|
Sign up to set email alerts
|

Iranian EFL Learners' Willingness to Communicate across Different Context- and Receiver-Types

Abstract: Willingness to communicate is the most basic orientation toward communication. Almost anyone is likely to respond to a direct question, but many will not continue or initiate interaction. This paper investigates Iranian EFL learners' perceptions of their willingness to initiate communication across four types of context and three types of receiver. The study employed a questionnaire consisting of 20 situations in which a person might choose to communicate or not to communicate. The study concludes that learner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Research into willingness to communicate (WTC) has been increasingly thriving since its first application to the field of second language acquisition (SLA) in the 1990s (Peng, 2013). WTC as a goal of foreign language learning and teaching has drawn the attention of language researchers and language practitioners in recent years (see, for example, Peng, 2012;Peng, 2013, Riasati, 2012Barjesteh et al, 2012;Fu & Wang, 2012;Khany & Nejad, 2016;Macintyre, 2007;Macintyre et al, 2011;Mirzane & Khabiri, 2016;Nazari & Allahyar, 2012;Zarrinabadi & Abdi, 2011, Eddy-U, 2015Zarrinabadi et al, 2014;Kamdideh & Barjesteh, 2019;and Léger & Storch, 2009). Macintyre (2007, p. 564) asserts that a degree of willingness to communicate (WTC) with the potential to rise and fall rapidly as the situation changes.…”
Section: Introductionmentioning
confidence: 99%
“…Research into willingness to communicate (WTC) has been increasingly thriving since its first application to the field of second language acquisition (SLA) in the 1990s (Peng, 2013). WTC as a goal of foreign language learning and teaching has drawn the attention of language researchers and language practitioners in recent years (see, for example, Peng, 2012;Peng, 2013, Riasati, 2012Barjesteh et al, 2012;Fu & Wang, 2012;Khany & Nejad, 2016;Macintyre, 2007;Macintyre et al, 2011;Mirzane & Khabiri, 2016;Nazari & Allahyar, 2012;Zarrinabadi & Abdi, 2011, Eddy-U, 2015Zarrinabadi et al, 2014;Kamdideh & Barjesteh, 2019;and Léger & Storch, 2009). Macintyre (2007, p. 564) asserts that a degree of willingness to communicate (WTC) with the potential to rise and fall rapidly as the situation changes.…”
Section: Introductionmentioning
confidence: 99%
“…(cf. McCroskey & Baer, 1985 In another study on Iranian students' WTC, Barjesteh, H., Vaseghi, R., and Neissi, S. (2012) indicated that learners are much more willing to communicate in group discussions and meetings with friends than other situations. They conclude that Iranian students are willing to initiate communication in situations experienced before, like group discussion or communicating with their friends.…”
Section: Willingness To Communicatementioning
confidence: 99%
“…Their lack of familiarity with the situation may also be influential. Unfamiliarity probably makes learners less confident and more insecure in a way that they prefer to withdraw a communicative encounter (Barjasteh, Vaseghi, & Neissi, 2012). Consequently, it is highly suggested that such factors should be avoided to the extent possible in academic contexts.…”
Section: Resultsmentioning
confidence: 99%